Evaluation of the predictive performance of the Liu type estimator. Issue 4 (21st April 2017) - Dawoud, Issam; Kaçiranlar, Selahattin
ABSTRACT: This article discusses the predictive performance of the Liu type (LT) estimator compared to ordinary least squares, principal components, ridge regression, and Liu estimators. The theoretical results are illustrated by a numerical example and a region is established where the LT estimator is uniformly superior to the other mentioned estimators.